Tolerance Communication: Local Government Law, FKUB Dialogue Skills, and Social Harmonization in Singkawang City - saliro, srisudonosaliro; Marilang, Marilang; Kurniati, Kurniati (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2021)
This paper aims to describe and analyze the reality of the involvement of local governments in legal aspects that have a function as a means of connecting dialogue that the Singkawang City FKUB will carry out within the framework of maintaining social harmonization between religious communities in this city. This paper will focus on the communication of tolerance carried out by FKUB based on the means of legislation and regulations set by the local government. This type of research is qualitative, and the technique of obtaining data is using observations and interviews. This paper finds that local government laws related to harmonization are contained in the Regional Regulation on the RPJMD and the Mayor's Decree. FKUB's efforts in building social harmonization are by establishing FKPELA and FK. PLATO as a more specific forum for dialogue. The absence of other regional laws and regulations on harmonization arrangements as a derivative form of the RPJMD makes the tolerance communication built by the provincial government unable to connect for FKUB to innovate in conducting a dialogue about tolerance. Thus, the involvement of local governments in the harmonization aspect is only limited to slogans and formalities and places more emphasis on the role of FKUB.